Examining Trends and Social Complexity of Clean and Healthy Living Behavior through Bibliometric Analysis - Pamungkas, Martinus Danang; Anwariyah, Hilya Raudhotul (Departemen Sosiologi Universitas Gadjah Mada, 2024)
Clean and Healthy Living Behavior (CHLB) provides information, education, and empowerment to encourage individuals, families, groups, and communities to adopt healthier lifestyles and minimize disease risk. Despite its crucial role in health, CHLB implementation in Indonesia is still low, with various studies highlighting inadequate CHLB practices among students and households. We conducted a bibliometric analysis to explore research results and identify trends and social complexity of CHLB. This study reports a bibliometric analysis through a systematic search of academic literature applying the CHLB theme. Bibliographic data were retrieved from the Scopus database on June 18, 2024, and then analyzed using the Bibliometrix R package. The 131 publications focused on journal articles, conference papers, and reviews in English, which were then collected and analyzed based on publication trends, influential articles, country contributions, and theme development. The authors also interpreted and synthesized the results of the bibliometric description of CHLB using Ulrich Beck's risk society theory. Articles on CHLB are published in 11 influential journals, with Indonesian authors contributing the most articles with 447 frequencies, followed by the USA (14 frequencies), China (11 frequencies), and Netherlands (11 frequencies). As part of the CHLB research hotspots, ten research areas and nine motor themes were presented, such as COVID-19, alternative medicine, pandemic, knowledge, diabetes mellitus, attitude and practice, education, empowerment, and environmental health. Using Ulrich Beck's risk society theory, this study also highlights how uncertainty and social complexity affect the implementation of CHLB in Indonesia.